6xxx aluminum alloys
The novel 6xxx aluminum lithium alloys address the challenge of improving multiple properties in aluminum alloys by optimizing the composition and ratios of key elements, resulting in enhanced strength, formability, and corrosion resistance.
Patent Information
- Application Number
- JP2024229781
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2018-12-05
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-23
AI Technical Summary
Aluminum alloys, particularly 6xxx series, face challenges in improving one property without degrading another, such as increasing strength while maintaining corrosion resistance and formability.
The development of novel 6xxx aluminum lithium alloys with specific compositions, including 0.65-0.85% Si, 0.40-0.59% Mg, and controlled ratios of Mg to Si, along with other elements like Fe, Mn, Cu, Cr, Zr, Ti, Zn, and V, to achieve improved combinations of strength, formability, bending, and corrosion resistance.
These alloys demonstrate enhanced mechanical properties, including increased tensile yield strength, improved formability, and maintained corrosion resistance, achieving a balanced combination of properties not readily attainable in conventional alloys.
Smart Images

Figure 2025066714000001_ABST
Abstract
Description
[Background technology]
[0001] Aluminum alloys are useful in a variety of applications. However, it is often difficult to improve one property of an aluminum alloy without degrading another. For example, it is difficult to increase the strength of an alloy without decreasing the alloy's corrosion resistance. Other properties of interest for aluminum alloys include formability and critical fracture strain, to name two. Summary of the Invention
[0002] In a broad sense, the present disclosure relates to novel 6xxx aluminum alloys having improved combinations of properties, such as, inter alia, improved combinations of strength, formability, bending, and / or corrosion resistance.
[0003] i.Composition Generally, the new 6xxx aluminum lithium alloys comprise (and in some examples consist essentially of, or consist of) 0.65-0.85 wt.% Si, 0.40-0.59 wt.% Mg (with a ratio of wt.% Mg to wt.% Si of 0.47:1 to 0.90:1 (Mg:Si)), 0.05-0.35 wt.% Fe, 0.04-0.13 wt.% Mn, 0-0.20 wt.% Cu, 0-0.15 wt.% Cr, 0-0.15 wt.% Zr, 0-0.10 wt.% Ti, 0-0.05 wt.% V, and 0-0.05 wt.% Zn, with the balance being aluminum and impurities.
[0004] The amount of magnesium (Mg) and silicon (Si) in the new 6xxx aluminum alloys may be associated with an improved combination of properties (e.g., strength, formability). Generally, the new 6xxx aluminum alloys include 0.40-0.59 wt.% Mg. In one embodiment, the new 6xxx aluminum alloys include at least 0.425 wt.% Mg. In another embodiment, the new 6xxx aluminum alloys include at least 0.45 wt.% Mg. In yet another embodiment, the new 6xxx aluminum alloys include at least 0.475 wt.% Mg. In another embodiment, the new 6xxx aluminum alloys include at least 0.50 wt.% Mg. In one embodiment, the new 6xxx aluminum alloys include up to 0.57 wt.% Mg. In one embodiment, the new 6xxx aluminum alloys include 0.49-0.59 wt.% Mg.
[0005] Typically, the new 6xxx aluminum alloys include 0.65-0.85 wt.% Si. In one embodiment, the new 6xxx aluminum alloys include at least 0.675 wt.% Si. In another embodiment, the new 6xxx aluminum alloys include at least 0.70 wt.% Si. In one embodiment, the new 6xxx aluminum alloys include up to 0.825 wt.% Si. In another embodiment, the new 6xxx aluminum alloys include up to 0.80 wt.% Si. In one embodiment, the new 6xxx aluminum alloys include 0.70-0.80 wt.% Si.
[0006] In general, the novel 6xxx aluminum alloys include silicon and magnesium such that the weight ratio of magnesium to silicon is between 0.47:1 and 0.90:1, i.e., the ratio of weight percent Mg to weight percent Si is between 0.47:1 and 0.90:1 (Mg:Si). In one embodiment, the ratio of weight percent Mg to weight percent Si is at least 0.50:1 (Mg:Si). In another embodiment, the ratio of weight percent Mg to weight percent Si is at least 0.52:1 (Mg:Si). In yet another embodiment, the ratio of weight percent Mg to weight percent Si is at least 0.54:1 (Mg:Si). In another embodiment, the ratio of weight percent Mg to weight percent Si is at least 0.56:1 (Mg:Si). In yet another embodiment, the ratio of weight percent Mg to weight percent Si is at least 0.58:1 (Mg:Si). In another embodiment, the ratio of weight percent Mg to weight percent Si is at least 0.60:1 (Mg:Si). In one embodiment, the ratio of weight percent Mg to weight percent Si is 0.88:1 or less (Mg:Si). In another embodiment, the ratio of weight percent Mg to weight percent Si is 0.86:1 or less (Mg:Si). In yet another embodiment, the ratio of weight percent Mg to weight percent Si is 0.84:1 or less (Mg:Si). In another embodiment, the ratio of weight percent Mg to weight percent Si is 0.82:1 or less (Mg:Si). In one embodiment, the ratio of weight percent Mg to weight percent Si is between 0.61:1 and 0.84:1 (Mg:Si).
[0007] Iron (Fe) is generally included in the new 6xxx aluminum alloys in the range of 0.05-0.35 wt.% Fe. In one embodiment, the new 6xxx aluminum alloys include at least 0.08 wt.% Fe. In another embodiment, the new 6xxx aluminum alloys include at least 0.10 wt.% Fe. In yet another embodiment, the new 6xxx aluminum alloys include at least 0.12 wt.% Fe. In another embodiment, the new 6xxx aluminum alloys include at least 0.15 wt.% Fe. In one embodiment, the new 6xxx aluminum alloys include up to 0.32 wt.% Fe. In another embodiment, the new 6xxx aluminum alloys include up to 0.30 wt.% Fe. In yet another embodiment, the new 6xxx aluminum alloys include up to 0.28 wt.% Fe. In one embodiment, the new 6xxx aluminum alloys include 0.09-0.26 wt.% Fe.
[0008] The amount of manganese (Mn) in the new 6xxx aluminum alloys may be associated with an improved combination of properties (e.g., formability). Generally, the new 6xxx aluminum alloys include 0.04-0.13 wt.% Mn. In one embodiment, the new 6xxx aluminum alloys include at least 0.05 wt.% Mn. In another embodiment, the new 6xxx aluminum alloys include at least 0.06 wt.% Mn. In one embodiment, the new 6xxx aluminum alloys include no more than 0.12 wt.% Mn. In another embodiment, the new 6xxx aluminum alloys include no more than 0.11 wt.% Mn. In another embodiment, the new 6xxx aluminum alloys include no more than 0.10 wt.% Mn. In one embodiment, the new 6xxx aluminum alloys include 0.06-0.10 wt.% Mn.
[0009] The new 6xxx aluminum alloys may optionally include copper (Cu), in an amount of up to 0.20 wt.% Cu (e.g., for strengthening purposes). In one embodiment, the new 6xxx aluminum alloys include at least 0.02 wt.% Cu. In another embodiment, the new 6xxx aluminum alloys include at least 0.04 wt.% Cu. In yet another embodiment, the new 6xxx aluminum alloys include at least 0.06 wt.% Cu. In another embodiment, the new 6xxx aluminum alloys include at least 0.07 wt.% Cu. In yet another embodiment, the new 6xxx aluminum alloys include at least 0.08 wt.% Cu. In another embodiment, the new 6xxx aluminum alloys include at least 0.09 wt.% Cu. In one embodiment, the new 6xxx aluminum alloys include no more than 0.19 wt.% Cu. In another embodiment, the new 6xxx aluminum alloys include no more than 0.18 wt.% Cu. In yet another embodiment, the novel 6xxx aluminum alloys include up to 0.17 wt.% Cu. In one embodiment, the novel 6xxx aluminum alloys include 0.09-0.17 wt.% Cu.
[0010] The new 6xxx aluminum alloys may optionally include chromium (Cr), in an amount up to 0.15 wt.% Cr (e.g., for grain structure control). In one embodiment, the new 6xxx aluminum alloys include at least 0.01 wt.% Cr. In another embodiment, the new 6xxx aluminum alloys include at least 0.02 wt.% Cr. In one embodiment, the new 6xxx aluminum alloys include 0.10 wt.% or less Cr. In another embodiment, the new 6xxx aluminum alloys include 0.08 wt.% or less Cr. In yet another embodiment, the new 6xxx aluminum alloys include 0.06 wt.% or less Cr. In another embodiment, the new 6xxx aluminum alloys include 0.05 wt.% or less Cr. In one embodiment, the new 6xxx aluminum alloys include 0.01-0.05 wt.% Cr.
[0011] The new 6xxx aluminum alloys may optionally include zirconium (Zr), in an amount up to 0.15 wt.% Zr (e.g., for grain structure control). In one embodiment, the new 6xxx aluminum alloys include 0.10 wt.% Zr or less. In another embodiment, the new 6xxx aluminum alloys include 0.05 wt.% Zr or less. In yet another embodiment, the new 6xxx aluminum alloys include 0.03 wt.% Zr or less. In another embodiment, the new 6xxx aluminum alloys include 0.01 wt.% Zr or less.
[0012] The new 6xxx aluminum alloys may include up to 0.15 wt% Ti. Titanium (Ti) may optionally be present in the new 6xxx aluminum alloys, such as for grain refinement purposes. In one embodiment, the new 6xxx aluminum alloys include at least 0.005 wt% Ti. In another embodiment, the new 6xxx aluminum alloys include at least 0.010 wt% Ti. In yet another embodiment, the new 6xxx aluminum alloys include at least 0.0125 wt% Ti. In one embodiment, the new 6xxx aluminum alloys include no more than 0.10 wt% Ti. In another embodiment, the new 6xxx aluminum alloys include no more than 0.08 wt% Ti. In yet another embodiment, the new 6xxx aluminum alloys include no more than 0.05 wt% Ti. In one embodiment, the target amount of titanium in the new 6xxx aluminum alloys is 0.03 wt% Ti. In one embodiment, the new 6xxx aluminum alloys include 0.01-0.05 wt% Ti.
[0013] Zinc (Zn) may optionally be present in the new 6xxx aluminum alloys in an amount up to 0.10 wt.% Zn. In one embodiment, the new alloys contain up to 0.05 wt.% Zn. In another embodiment, the new alloys contain up to 0.03 wt.% Zn. In another embodiment, the new alloys contain up to 0.01 wt.% Zn.
[0014] Vanadium (V) may optionally be present in the new 6xxx aluminum alloys in an amount of up to 0.05 wt.% V. In one embodiment, the new 6xxx aluminum alloys contain up to 0.03 wt.% V. In another embodiment, the new 6xxx aluminum alloys contain up to 0.01 wt.% V.
[0015] As discussed above, the balance of the novel aluminum alloys is generally aluminum and impurities. In one embodiment, the 6xxx aluminum alloys contain no more than 0.15 wt.% total impurities, and the 6xxx aluminum alloys contain no more than 0.05 wt.% each of the impurities. In another embodiment, the 6xxx aluminum alloys contain no more than 0.10 wt.% total impurities, and the 6xxx aluminum alloys contain no more than 0.03 wt.% each of the impurities.
[0016] Unless otherwise stated, when indicating an amount of an element, the expression "maximum" means that the elemental composition is optional, including an amount of zero of that particular compositional component. Unless otherwise stated, all compositional percentages are in weight percent (wt%).
[0017] ii. Processing and product form The new 6xxx aluminum alloys may be useful in a variety of product forms, including ingots or billets, wrought product forms (sheet, plate, forgings, and extrusions), molded castings, additively manufactured products, and powder metallurgy products. In one embodiment, the new 6xxx aluminum alloys are rolled products. For example, the new 6xxx aluminum alloys may be produced in sheet form. In one embodiment, the sheet made from the new 6xxx aluminum alloys has a thickness of 1.5 mm to 4.0 mm.
[0018] In one embodiment, the new 6xxx aluminum alloys are produced using ingot casting and hot rolling. In one embodiment, the method includes the steps of casting an ingot of the new 6xxx aluminum alloy, homogenizing the ingot, rolling the ingot into a rolled product having a final gauge (by hot rolling and / or cold rolling), solution heat treating the rolled product, where the solution heat treating includes heating the rolled product to a temperature and for a time such that some or substantially all of the Mg2Si of the rolled product is dissolved into solid solution, and quenching (e.g., water or air quench) the rolled product after the solution heat treating. After quenching, the rolled product may be artificially aged. In some embodiments, one or more annealing steps may be completed before or after the rolling steps (e.g., hot rolling to a first gauge, annealing, cold rolling to a final gauge). The artificially aged product may be painted (e.g., for automotive parts) and therefore subjected to a bake paint cycle. In one embodiment, rolled aluminum alloy products made from the new alloy may be incorporated into automobiles.
[0019] In one embodiment, the novel 6xxx aluminum alloy products are cast by continuous casting. Downstream of the continuous casting, the product may be (a) rolled (hot and / or cold), (b) optionally annealed (e.g., after hot rolling and before any cold rolling step), (c) solution heat treated and quenched, (d) optionally cold worked (after solution heat treatment), and e) artificially aged, all steps (a)-(e) may be performed in-line or offline to the continuous casting process. Some methods for producing the novel 6xxx aluminum alloy products using continuous casting and associated downstream processes are described, for example, in U.S. Pat. No. 7,182,825, U.S. Patent Application Publication No. 2014 / 0000768, and U.S. Patent Application Publication No. 2014 / 036998, each of which is incorporated herein by reference in its entirety. The artificially aged product may be painted (eg, for automotive parts) and therefore subjected to a bake paint cycle.
[0020] In one embodiment, hot rolling includes hot rolling to an intermediate gauge product, which exits the hot rolling mill at a temperature of 290° C. or less. After hot rolling, optional annealing may be completed. After hot rolling and optional annealing, the intermediate gauge product may be cold rolled to final gauge.
[0021] In another embodiment, hot rolling includes rolling to an intermediate gauge product, which exits the hot rolling mill at a temperature of 400-480° C. After hot rolling, the intermediate gauge product may then be cold rolled to final gauge, i.e., in this embodiment, no annealing is required after hot rolling and before cold rolling.
[0022] Once cold rolling is completed, cold rolling generally involves reducing the intermediate gauge thickness to a final gauge thickness. In one embodiment, cold rolling involves at least a 50% cold reduction. In another embodiment, cold rolling involves at least a 60% cold reduction. In yet another embodiment, cold rolling involves at least a 65% cold reduction. In one embodiment, the cold rolling is no greater than 85%.
[0023] As known to those skilled in the art, "cold rolled XX%" and the like means XX CR % means XX CR % is the amount of thickness reduction achieved when an aluminum alloy body is reduced from a first thickness of T1 to a second thickness of T2, where T1 is the intermediate gauge thickness and T2 is the thickness. In other words, XX CR % is equal to: XX CR %=(1-T2 / T1)*100% For example, when an aluminum alloy body is cold rolled from a first thickness (T1) of 15.0 mm to a second thickness (T2) of 3.0 mm, XX CR % is 80%. Phrases such as "80% cold rolled" and "80% cold rolled" are CR This is equivalent to displaying %=80%.
[0024] In one embodiment, the peak metal temperature during the solution heat treatment is in the range of 504° C. to 593° C. The peak metal temperature is the highest temperature achieved by the alloy product during the solution heat treatment.
[0025] In one embodiment, the new 6xxx aluminum alloy products are processed to the T4 temper as defined by ANSI H35.1(2009), i.e., the new 6xxx is solution heat treated, then quenched, and then naturally aged to a substantially stable condition. In one embodiment, the amount of natural aging is 30 days, and the T4 properties of the new 6xxx aluminum alloys are measured at 30 days of natural aging.
[0026] In one embodiment, the new 6xxx aluminum alloy is processed to a T6 temper as defined by ANSI H35.1(2009), i.e., the new 6xxx is solution heat treated, then quenched, and then artificially aged. In one embodiment, the artificial aging comprises baking a finish. In one embodiment, the artificial aging comprises baking a finish. In one embodiment, the baking comprises heating the new 6xxx aluminum alloy article to 180°C and then holding for 20 minutes.
[0027] In one embodiment, the new 6xxx aluminum alloy is worked to a T8 temper as defined by ANSI H35.1(2009), i.e., the new 6xxx is solution heat treated, then quenched, then cold worked (e.g., stretched), and then artificially aged. In one embodiment, the artificial aging comprises baking a finish. In one embodiment, the artificial aging comprises baking a finish. In one embodiment, the baking comprises heating the new 6xxx aluminum alloy article to 180° C. and then holding for 20 minutes.
[0028] iii. Microstructure A. Recrystallization The steps of processing the new 6xxx aluminum alloys may be accomplished such that the new aluminum alloy body products achieve a predominantly recrystallized microstructure. A predominantly recrystallized microstructure means that the aluminum alloy body contains at least 51% recrystallized grains (by volume fraction). The degree of recrystallization of the new 6xxx aluminum alloy products may be determined using a suitable metallographic specimen of the material analyzed using EBSD with a suitable SEM and computer software to determine grain misorientation. In one embodiment, the new 6xxx aluminum alloy products are at least 60% recrystallized. In another embodiment, the new 6xxx aluminum alloy products are at least 70% recrystallized. In yet another embodiment, the new 6xxx aluminum alloy products are at least 80% recrystallized. In another embodiment, the new 6xxx aluminum alloy products are at least 90% recrystallized. In yet another embodiment, the new 6xxx aluminum alloy products are at least 95% recrystallized. In another embodiment, the new 6xxx aluminum alloy products are at least 98% recrystallized or more.
[0029] B. Grain size and texture The new 6xxx aluminum alloy products may achieve a fine grain size. In one embodiment, the new 6xxx aluminum alloy products achieve an area weighted average grain size of 45 micrometers or less. In another embodiment, the new 6xxx aluminum alloy products achieve an area weighted average grain size of 40 micrometers or less. In one embodiment, the new 6xxx aluminum alloy products achieve an area weighted average grain size of at least 20 micrometers. In another embodiment, the new 6xxx aluminum alloy products achieve an area weighted average grain size of at least 25 micrometers. In yet another embodiment, the new 6xxx aluminum alloy products achieve an area weighted average grain size of at least 30 micrometers.
[0030] The new 6xxx aluminum alloy products may achieve a unique texture. Texture refers to the preferred orientation of at least some of the grains of a crystalline structure. Using matchsticks as an analogy, consider a material composed of matchsticks. If the matchsticks are contained within a material in a completely random manner, the material will have a random texture. However, if the heads of at least some of those matchsticks are aligned, pointing in the same direction, like a compass pointing north, the material will have at least some texture due to the aligned matchsticks. The same principle applies to the grains of a crystalline material.
[0031] Texture components resulting from the manufacturing of aluminum alloy products may include one or more of copper, S texture, brass, cube, and Goss texture, to name a few. Each of these texture components is defined in Table 1 below. [Table a]
[0032] The following table provides non-limiting examples of texture constituents and ranges that may be achieved by the new 6xxx aluminum alloys disclosed herein. [Table b]
[0033] For purposes of this patent application, grain size and texture shall be measured and normalized as follows: A Phillips XL-30 FESEM or equivalent is used. Electron Backscatter Diffraction (EBSD) patterns are collected using an EDAX EBSD Digiview 5 detector system, or equivalent. EBSD acquisition is performed using EDAX TSL EBSD Data Collection (OIM)™ software, version 7, or equivalent. The specimens are sectioned and polished for analysis in the long (L) × short transverse (ST) plane and prepared for standard metallographic analysis, for example, by grinding the plane of the sectioned and mounted specimen and polishing it with successive finer grits to 0.05 μm colloidal silica (SiO2). The final step is vibratory polishing for 45 min. After metallographic preparation, the sample is ion milled for 15 min using a suitable broad beam argon ion milling system (e.g., Hitachi IM4000Plus) operated at 3 kV and a grazing angle incidence (10 degrees) on the sample surface while rotating the sample at 25 revolutions per minute. Data acquisition parameters include an electron beam energy of 20 kV, a spot size of 5 with a sample tilt angle of 70 degrees, a 0.8 micrometer step size and a square grid scan type is used. ·EBSD patterns are collected using 8x8 binning and image correction processing, including background subtraction and normalized intensity histograms. Map dimensions are 800 micrometers full thickness in the transverse (ST) direction and 800 micrometers in the longitudinal (L) direction (i.e., rolling direction of the sheet product). · The software used to analyze the acquired data should be EDAX TSL OIM™ 8 Data Analysis Package or similar. The data analysis included a two-step cleanup procedure. The first step was a Neighbor Orientation Correlation level 2 cleanup applied to the data with a minimum Confidence Index (CI) of 0.1 and a particle acceptance angle of 5 degrees. The second step was the Grain Dilation method using a particle acceptance angle of 5 degrees and a minimum of 5 points per particle for one replicate. Particles are defined to have a minimum of 5 points per particle with a particle acceptance angle of 5 degrees. In one embodiment, the software determines particle size (average particle diameter) generally via the Heyn linear intercept method per ASTM E112-12, §13. In another embodiment, individual particle sizes are determined by counting the number of points within each particle and multiplying by the area of each point (the square of the step size). The following equation may be used to calculate particle size (i.e. equivalent circular diameter):
number
number
number
[0034] iv.Properties As noted above, the new 6xxx aluminum alloys disclosed herein may realize an improved combination of properties. In one embodiment, the new 6xxx aluminum alloys realize a T4 tensile yield strength in the long transverse (LT) direction of 90-110 MPa. In one embodiment, the new 6xxx aluminum alloys realize a T4 uniform elongation in the long transverse (LT) direction of at least 21%. In one embodiment, the new 6xxx aluminum alloys realize a T4 n value in the long transverse (LT) direction of at least 0.245 (10-20%). For purposes of this paragraph, the T4 properties are measured after 30 days of natural aging.
[0035] For purposes of this patent application, tensile yield strength and uniform elongation are measured according to ASTM E8 and B557. For purposes of this patent application, "n-value (10-20%)" is measured according to ASTM E646 using a strain of 10-20%.
[0036] In one embodiment, the new 6xxx aluminum alloys realize a T6 (0% pre-strain / elongation) tensile yield strength of at least 160 MPa when artificially aged by baking a finish at 180° C. for 20 minutes. In another embodiment, the new 6xxx aluminum alloys realize a T6 (0% pre-strain / elongation) tensile yield strength of at least 170 MPa when artificially aged by baking a finish at 180° C. for 20 minutes. In yet another embodiment, the new 6xxx aluminum alloys realize a T6 (0% pre-strain / elongation) tensile yield strength of at least 180 MPa when artificially aged by baking a finish at 180° C. for 20 minutes.
[0037] In one embodiment, the new 6xxx aluminum alloys, when stretched by 1-3% after solution heat treatment and then artificially aged by baking at 180° C. for 20 minutes, achieve a T8 tensile yield strength of at least 215 MPa.
[0038] In one embodiment, the new 6xxx aluminum alloys achieve a hem rating of 2 or greater. Hem ratings are defined in the Examples below. In another embodiment, the new 6xxx aluminum alloys achieve a hem rating of 1.
[0039] In one embodiment, the new 6xxx aluminum alloys achieve a VDA bend angle of at least 125°. The VDA test is performed by naturally aging the product for 30 days, then stretching the product 10% in the L (longitudinal) direction, and then performing a VDA bend test according to the VDA 238-100 bend test specification (https: / / www.vda.de / en / services / Publications / vda-238-100-plate-bending-test-for-metallic-materials.html). In another embodiment, the new 6xxx aluminum alloys achieve a VDA bend angle of at least 130°. In yet another embodiment, the new 6xxx aluminum alloys achieve a VDA bend angle of at least 135°. In another embodiment, the new 6xxx aluminum alloys achieve a VDA bend angle of at least 140°. In yet another embodiment, the new 6xxx aluminum alloys achieve a VDA bend angle of at least 143°.
[0040] In one embodiment, the new 6xxx aluminum alloys are free of Luders deformation. Luders deformation is tested by naturally aging the product for 8 days and then stretching the product 10% in the L (longitudinal) direction. If Luder lines are visible to the naked eye, the product is not free of Luders deformation. If Luder lines are not visible to the naked eye, the product is free of Luders deformation.
[0041] In one embodiment, the new 6xxx aluminum alloys achieve the combination of properties shown in the "Preferred Properties Box" of Figure 1. In some of these embodiments, the new 6xxx aluminum alloys achieve a VDA bend angle of at least 140°. Others of the properties identified above may also be achieved.
[0042] In one embodiment, the new 6xxx aluminum alloys achieve the combination of properties shown in the "Preferred Properties Box" of Figure 2. In some of these embodiments, the new 6xxx aluminum alloys achieve a VDA bend angle of at least 140°. Others of the properties identified above may also be achieved.
[0043] In one embodiment, the new 6xxx aluminum alloys achieve the combination of properties shown in the "Preferred Properties Box" of Figure 3. In some of these embodiments, the new 6xxx aluminum alloys achieve a VDA bend angle of at least 140°. Others of the properties identified above may also be achieved.
[0044] In one embodiment, the new 6xxx aluminum alloys achieve the combination of properties shown in the "Preferred Properties Box" of Figure 4. In some of these embodiments, the new 6xxx aluminum alloys achieve a VDA bend angle of at least 140°. Others of the above identified properties may also be achieved.
[0045] The figures constitute a part of this specification and include exemplary embodiments of the present invention, illustrating various objects and their features. In addition, any measurements, specifications, etc. shown in the figures are intended to be illustrative and not limiting. Thus, specific structural and functional details disclosed herein should not be construed as limiting, but merely as a representative basis for teaching those skilled in the art how to use the present invention in various ways.
[0046] Various embodiments to the present disclosure will be further described with reference to the accompanying drawings, in which like structures are designated by like numerals throughout the several views. The drawings shown are not necessarily to scale, with emphasis instead generally being placed upon illustrating the principles of the invention. Additionally, some features may be exaggerated to show details of particular components.
[0047] Among those advantages and improvements that have been disclosed, other objects and advantages of the present invention will become apparent from the following description taken in conjunction with the accompanying drawings. Detailed embodiments of the present invention are disclosed herein; however, it should be understood that the disclosed embodiments are merely illustrative of the invention that may be embodied in various forms. Moreover, the examples given in connection with the various embodiments of the present invention are intended to be illustrative and not limiting.
[0048] Throughout the specification and claims, the following terms take the meanings expressly associated therewith, unless the context clearly dictates otherwise. As used herein, the phrases "in one embodiment" and "in some embodiments" do not necessarily refer to the same embodiment(s), but may. Additionally, as used herein, the phrases "in another embodiment" and "in some other embodiments" do not necessarily refer to different embodiments, but may. Thus, as described below, various embodiments of the invention may be readily combined without departing from the scope or spirit of the invention.
[0049] Additionally, as used herein, the term "or" is an inclusive "or" and is equivalent to the term "and / or" unless the context clearly dictates otherwise. The term "based on" is not exclusive and may be based on additional factors not stated unless the context clearly dictates otherwise. Additionally, throughout this specification, the meanings of "a," "an," and "the" include plural references unless the context clearly dictates otherwise. The meaning of "in" includes "in" and "on," unless the context clearly dictates otherwise. [Brief description of the drawings]
[0050] [Figure 1] 1 is an image of the grain structure of alloy A1-1.
[0051] [Diagram 2]1 is an image of the grain structure of alloy A1-10.
[0052] [Diagram 3] 1 is an image of the grain structure of alloy A1-19.
[0053] [Figure 4] 1 is an image of the grain structure of alloy A1-22.
[0054] [Diagram 5] 1 is a graph showing tensile yield strength in as-is (T4) temper (after paint bake, no pre-strain, i.e., T6) versus n-value (10-20%) for various example alloys.
[0055] [Figure 6] 1 is a graph showing tensile yield strength in the as-is (T4) temper (after paint baking, no pre-strain, i.e., T6) versus uniform elongation for various example alloys.
[0056] [Figure 7] 1 is a graph showing tensile yield strength in as-is (T4) temper (after paint bake, 2% pre-strain, i.e., T8) versus n-value (10-20%) for various example alloys.
[0057] [Figure 8] 1 is a graph showing tensile yield strength in as-is (T4) temper (after paint bake, 2% pre-strain, i.e., T8) versus uniform elongation for various example alloys. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0058] The following examples are intended to illustrate the invention and should not be construed as limiting the invention in any way.
[0059] Example 1: Alloy Composition Aluminum alloys having the compositions shown in Table 1 below were cast as ingots. [Table 1]
[0060] The ingots were then homogenized and then hot rolled to an intermediate gauge with an exit temperature of 290°C or less. The alloys were then cold rolled to a final gauge of 0.95 or 1.2 mm. The cold roll reduction (reduction from intermediate to final gauge) is provided in Table 2 below. The final gauge products were then solution heat treated by heating to various peak metal temperatures (shown in Table 2) after which the alloys were immediately air quenched. After quenching, some alloys were stretched while others were not, as shown in Table 2. All alloys were then naturally aged for 30 days, after which some alloys were then stretched, and after which some alloys (both stretched and non-stretched) were artificially aged by heating to 180°C and then holding at this temperature for 20 minutes and then cooling to room temperature. A 2% stretch (pre-strain) was completed in the laboratory to simulate a typical forming operation.
[0061] The mechanical properties of the alloys in various tempers (T4, T6, T8) were then measured and the results are provided in Table 3 below. Mechanical properties were tested according to ASTM E8, ASTM B557. All reported mechanical property values are in the LT (long transverse) direction and are based on an average of six specimens unless otherwise indicated. "n-values" were measured according to ASTM E646 using strains of 10-20%. [Table 2-1] [Table 2-2] [Table 3-1] [Table 3-2]
[0062] For all processing conditions, the alloys of the present invention achieved higher tensile yield strength (TYS) and ultimate yield strength (UTS) than the non-invention alloys. In addition, the alloys of the present invention exhibited less strength loss at lower peak metal temperatures. The alloys of the present invention also generally had higher elongations and higher n-values than the non-invention alloys under most processing conditions, demonstrating improved formability.
[0063] Example 2: Heme performance test Selected Example 1 alloys were tested for hemming performance by stretching 15% in the L direction followed by flat hem testing. Stretching was completed on alloys that had been naturally aged for 30 days and without subsequent artificial aging, i.e., the alloys were in T4 temper prior to the 15% stretch. Four hems were completed for each processing condition. The hem ratings were then assessed according to the following scale: [Table c] Table 4 below shows the hem ratings achieved for the A1 and A2 alloys. [Table 4]
[0064] The A1 alloy has more iron than the A2 alloy. Industry observers associate higher iron content with poorer hemming performance. However, the A1 alloy demonstrated better hemming performance than the A2 alloy. Additionally, the higher iron content improved hemming performance in samples with lower levels of cold work (e.g., alloys A1-22, A1-23, and A1-24, with 65% cold work, demonstrated the same hemming performance as alloys A1-10, A1-11, and A1-12, which were the same gauge but only 81% cold work).
[0065] <Example 3: VDA bending performance test> Selected Example 1 was stretched 10% in the L direction and tested according to VDA 238-100 bending test specification (https: / / www.vda.de / en / services / Publications / vda-238-100-plate-bending-test-for-metallic-materials.html). VDA stands for "Verband der Automobilindustrie" (German Association of the Automotive Industry). Stretching was completed on alloys that had been naturally aged for 30 days and without artificial aging thereafter, i.e., the alloys were in T4 temper prior to the 10% stretch. Table 5 below shows the VDA bend test results for Selected Example 2 alloys. [Table 5]
[0066] At 65% cold work, the A1 alloy showed improved bending over the A2 alloy. It is believed that at least the difference in iron content contributed to this difference in properties. (The 2° difference is the material difference at these levels of achieved bend angle.)
[0067] <Example 4: Luders transformation> Selected samples of Example 1 alloy were naturally aged for 8 days and then stretched 10% in the LT direction before a coating of paint was applied. After painting, the alloys were examined to determine whether Luders bands were present. Table 6 below shows the tensile yield strength and Luders band results for selected Example 2 alloys. [Table 6]
[0068] As shown in Table 6, only the non-invention alloys showed the presence of Luders bands. For the range of alloy processing, the invention alloys did not have any Luders bands.
[0069] Example 5: Texture and grain size Grain size and texture measurements of selected A1 samples from Example 2 were obtained via electron backscattering detection in a scanning electron microscope. The results of the grain size and texture measurements are shown in Table 7 below. Additionally, grain structure images obtained via SEM are shown in Figures 1-4. [Table 7]
[0070] Table 7 shows that with higher levels of cold work, the A1 alloy has a finer (smaller) grain structure and a higher level of cube texture. Figures 1-4 show grain structure images obtained via SEM for alloys A1-1, A1-10, A1-19, and A1-22. The weighted average grain sizes obtained from these images for alloys A1-1, A1-10, A1-19, and A1-22 were 32 μm, 32 μm, 34 μm, and 41 μm, respectively. Again, with higher levels of cold work, the A1 alloy has a finer (smaller) grain structure. When comparing the invention alloys and non-invention alloys with the same processing for grain size measurement, alloy A1-1 had a coarser grain structure than alloy B1-1.
[0071] Thus, in some embodiments, the novel alloys disclosed herein can have a grain size area weighted average of 20 micrometers to 45 micrometers, hi one embodiment, the novel alloys have a grain size of 30 to 40 micrometers.
[0072] In some embodiments, the new alloys disclosed herein may be in sheet form and have the following texture characteristics: [Table d]
[0073] While various embodiments of the present disclosure have been described in detail, it will be apparent that modifications and variations of these embodiments will occur to those skilled in the art, but it should be expressly understood that such modifications and variations are within the spirit and scope of the present disclosure.
Claims
1. 6xxx aluminum alloys, 0.65 to 0.85 wt.% Si; 0.40 to 0.59 wt.% Mg; ((wt%) Mg / (wt%) Si is 0.47 to 0.90), 0.05 to 0.35 wt. % Fe; 0.04 to 0.13 wt.% Mn; 0 to 0.20 wt.% Cu; 0 to 0.15 wt.% Cr; 0 to 0.15 wt. % Zr; 0 to 0.15 wt. % Ti; 0 to 0.10 wt. % Zn; and 0 to 0.05 wt. % V; 6xxx aluminum alloys, the balance being aluminum and impurities.
2. 2. The 6xxx aluminum alloy of claim 1, wherein the 6xxx aluminum alloy contains at least 0.675 wt.% Si, or at least 0.70 wt.% Si.
3. 3. The 6xxx aluminum alloy of claim 1, wherein the 6xxx aluminum alloy contains up to 0.825 wt.% Si, or up to 0.80 wt.% Si.
4. The 6xxx aluminum alloy of any one of claims 1 to 3, wherein the 6xxx aluminum alloy contains at least 0.425 wt.% Mg, or at least 0.45 wt.% Mg, 0.475 wt.% Mg, or at least 0.50 wt.% Mg.
5. The 6xxx aluminum alloy of any one of the preceding claims, wherein the 6xxx aluminum alloy contains up to 0.57 wt. % Mg.
6. The 6xxx aluminum alloy according to any one of the preceding claims, wherein the (wt % Mg) / (wt % Si) is at least 0.50, or at least 0.52, or at least 0.54, or at least 0.56, or at least 0.58, or at least 0.
60.
7. The 6xxx aluminum alloy according to any one of the preceding claims, wherein the (wt %) Mg / (wt %) Si is 0.88 or less, or 0.86 or less, or 0.84 or less, or 0.82 or less.
8. The 6xxx aluminum alloy of any one of the preceding claims, wherein the 6xxx aluminum alloy contains at least 0.08 wt. % Fe.
9. 9. The 6xxx aluminum alloy of any one of the preceding claims, wherein the 6xxx aluminum alloy contains up to 0.32 wt.% Fe, or up to 0.28 wt.% Fe, or up to 0.26 wt.% Fe.
10. The 6xxx aluminum alloy of any one of the preceding claims, wherein the 6xxx aluminum alloy contains at least 0.02 wt.% Cu, or at least 0.04 wt.% Cu, or at least 0.06 wt.% Cu, or at least 0.07 wt.% Cu, or at least 0.08 wt.% Cu, or at least 0.09 wt.% Cu.
11. 11. The 6xxx aluminum alloy of any one of claims 1-10, wherein the 6xxx aluminum alloy contains up to 0.19 wt.% Cu, or up to 0.18 wt.% Cu, or up to 0.17 wt.% Cu.
12. The 6xxx aluminum alloy of any one of the preceding claims, wherein the 6xxx aluminum alloy contains at least 0.05 wt.% Mn or at least 0.06 wt.% Mn.
13. 13. The 6xxx aluminum alloy of any one of the preceding claims, wherein the 6xxx aluminum alloy contains up to 0.12 wt.% Mn, or up to 0.11 wt.% Mn, or up to 0.10 wt.% Mn.
14. The 6xxx aluminum alloy of any one of the preceding claims, wherein the 6xxx aluminum alloy contains at least 0.01 wt.% Cr, or at least 0.02 wt.% Cr.
15. The 6xxx aluminum alloy of any one of the preceding claims, wherein the 6xxx aluminum alloy contains up to 0.10 wt.% Cr, or up to 0.08 wt.% Cr, or up to 0.06 wt.% Cr, or up to 0.05 wt.% Cr.
16. The 6xxx aluminum alloy of any one of the preceding claims, wherein the 6xxx aluminum alloy contains 0.10 wt.% Zr, or up to 0.05 wt.% Zr, or up to 0.03 wt.% Zr, or up to 0.01 wt.% Zr.
17. 17. The 6xxx aluminum alloy of any one of the preceding claims, wherein the 6xxx aluminum alloy contains up to 0.10 wt.% Ti, or up to 0.08 wt.% Ti, or up to 0.05 wt.% Ti.
18. 18. The 6xxx aluminum alloy of any one of the preceding claims, wherein the 6xxx aluminum alloy contains up to 0.05 wt.% Zn, or up to 0.03 wt.% Zn, or up to 0.01 wt.% Zn.
19. The 6xxx aluminum alloy of any one of the preceding claims, wherein the 6xxx aluminum alloy contains up to 0.03 wt.% V, or up to 0.01 wt.% V.
20. 20. The 6xxx aluminum alloy of any one of the preceding claims, wherein the 6xxx aluminum alloy contains less than or equal to 0.15 wt. % of said impurities in total, and the 6xxx aluminum alloy contains less than or equal to 0.05 wt. % of said impurities each.
21. 21. The 6xxx aluminum alloy of any one of the preceding claims, wherein the 6xxx aluminum alloy contains less than or equal to 0.10 wt. % of said impurities in total, and the 6xxx aluminum alloy contains less than or equal to 0.03 wt. % of said impurities each.
22. 6xxx aluminum alloys, 0.70 to 0.80 wt.% Si; 0.49 to 0.59 wt.% Mg; ((Mg weight%) / (Si weight%) is 0.61 to 0.84) 0.09 to 0.29 wt.% Fe; 0.06 to 0.10 wt. % Mn; 0.09 to 0.17 wt.% Cu; 0.01 to 0.05 wt.% Cr; 0.01 to 0.05 wt.% Ti; 0.05 wt.% or less of Zn; 0.05 wt.% or less of V; and 0.05 wt.% or less of Zr; 6xxx aluminum alloys, the balance being aluminum and impurities.
23. 1. A method comprising: (a) casting the 6xxx aluminum alloy of any one of claims 1-22 into a cast product; and (b) hot rolling the cast product into an intermediate gauge product; (i) the exit temperature of the intermediate gauge product is 290° C. or less and annealing of the intermediate gauge product is completed after the hot rolling; or (ii) hot rolling, wherein the exit temperature of the intermediate gauge product is between 400 and 480°C; (c) cold rolling the intermediate gauge product into a final gauge product; the intermediate gauge product has an as-received thickness; the final gauge product having a final thickness; The method of claim 1, wherein said cold rolling comprises reducing said as-received thickness by at least 50% to achieve said final thickness.
24. after said cold rolling, solution heat treating said final gauge product and then quenching; the solution heat treating comprises heating the final gauge product to a peak metal temperature; 24. The method of claim 23, wherein the peak metal temperature is less than or equal to 593°C.
25. 25. The method of claim 24, further comprising artificially aging the final gauge product after said quenching.
26. 25. The method of claim 24, wherein the artificial aging comprises baking a finish.
27. 24. The method of claim 23, further comprising naturally aging the final gauge product for at least 3 days after said quenching.
28. 24. The method of claim 23, wherein the final gauge product achieves a predominantly recrystallized microstructure.
29. 30. The method of claim 28, wherein the final gauge product achieves an area weighted average grain size of 45 micrometers or less, or 40 micrometers or less.
30. 30. The method of claim 29, wherein the final gauge product achieves an area weighted average grain size of at least 20 micrometers, or at least 25 micrometers, or at least 30 micrometers.
31. 30. The method of claim 28, wherein the final gauge product contains at least 10% cube texture.
32. 6xxx aluminium alloy sheet products, 0.65 to 0.85 wt.% Si; 0.40 to 0.59 wt.% Mg; ((Mg weight%) / (Si weight%) is 0.47 to 0.90) 0.05 to 0.35 wt. % Fe; 0.04 to 0.13 wt.% Mn; 0 to 0.20 wt.% Cu; 0 to 0.15 wt.% Cr; 0 to 0.15 wt. % Zr; 0 to 0.15 wt. % Ti; 0 to 0.10 wt. % Zn; and 0 to 0.05 wt. % V; The remainder is aluminum and impurities. The 6xxx aluminum alloy sheet product has a thickness of 1.5 to 4.0 mm; the 6xxx aluminum alloy sheet product has a predominantly recrystallized microstructure; said 6xxx aluminum alloy sheet product achieving a grain weighted average grain size of from 5 to 45 micrometers; 1. A 6xxx aluminum alloy sheet product, wherein the 6xxx aluminum alloy sheet product contains at least 10% cube texture.
Citation Information
Patent Citations
High volume edge and high baking hardening performance aluminum alloy sheet material and preparation method thereof
CN107881384A
Aluminum alloy sheet having excellent bending workability and production method thereof
JP2003226926A
Aluminum alloy sheet for forming, and manufacturing method therefor
JP2003268475A
Aluminum alloy sheet for molding, and method of producing the same
JP2004027253A
Aluminum alloy sheet having excellent formability, and its production method
JP2007077472A